A Comparative Study about Knowledge, Attitude, Practice of Antibiotic Use and Perceptions of the Possible Causes of Resistance between Final Year Undergraduate Students and Postgraduate Pharmacy Students (Medico Legal Update, 2021)
Background: Antibiotic resistance is a problem leading to difficulty in treating microbial infections thatmay occur due to many causes. For the important pharmacist role as a reference for the information and theability to access to medications, they are vital members in lowering the development of antibiotic resistance,and also they support the proper use and control of antibioticsmisuse. Our goal is comparing the knowledge,attitude, practice of undergraduate and postgraduate pharmacy students and their perceptions about thecausing factors of antibiotic resistance in Iraq.Method: A cross sectional study was conducted involving the final year bachelor and postgraduate (masterand Philosophical doctor) students from different private and public pharmacy universities in Iraq. Anadjusted questionnaire was administrated to 233 students electronically and the results obtained wereanalyzed by using SPSS 20 for Windows Descriptive. A significant difference was found in the knowledgeof antibiotic between undergraduate and postgraduate(Master and Philosophical doctor) students (Meanknowledge score5.32 versus 5.92 respectively, p